2014
DOI: 10.1016/j.juro.2013.06.122
|View full text |Cite
|
Sign up to set email alerts
|

Climacturia after Definitive Treatment of Prostate Cancer

Abstract: Climacturia is experienced by a substantial proportion of men after undergoing definitive treatment of prostate cancer. We found a complex relationship between stress urinary incontinence and climacturia, and noted that the presence of climacturia does not necessarily negatively impact sexual satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 20 publications
3
29
0
1
Order By: Relevance
“…Interestingly, recovery rates of 10% and 30% from PO were observed at 12 and 60 months after surgery, respectively, thus corroborating previous findings that demonstrated a decrease in the frequency and intensity of pain throughout the follow-up [33]. Although UI and EF impairment have been previously associated with orgasmic modifications after surgery [25293035], no data have suggested strong predictors for PO occurrence after RP; however, a significantly higher prevalence of PO after ORP than after RARP has been reported (9.5% vs. 11.6%; p=0.04) [31]. Similarly, in a series of 156 RARP cases, Tewari et al [34] reported that only 3.2% of patients complained of PO after treatment.…”
Section: Prevalence Of Orgasmic Dysfunctions After Radical Prostatectomysupporting
confidence: 86%
See 4 more Smart Citations
“…Interestingly, recovery rates of 10% and 30% from PO were observed at 12 and 60 months after surgery, respectively, thus corroborating previous findings that demonstrated a decrease in the frequency and intensity of pain throughout the follow-up [33]. Although UI and EF impairment have been previously associated with orgasmic modifications after surgery [25293035], no data have suggested strong predictors for PO occurrence after RP; however, a significantly higher prevalence of PO after ORP than after RARP has been reported (9.5% vs. 11.6%; p=0.04) [31]. Similarly, in a series of 156 RARP cases, Tewari et al [34] reported that only 3.2% of patients complained of PO after treatment.…”
Section: Prevalence Of Orgasmic Dysfunctions After Radical Prostatectomysupporting
confidence: 86%
“…Indeed, in an assessment of the potential predictors of climacturia, Frey et al [30] showed a higher risk of climacturia in patients with postoperative UI, and similar findings were observed by O'Neil et al [29] in patients treated with surgery or radiation therapy. Conversely, Nilsson et al [28] explored orgasm-associated incontinence in a consecutive series of 691 sexually active RP patients, of whom 268 reported climacturia despite recovering full UC in 86% of cases.…”
Section: Prevalence Of Orgasmic Dysfunctions After Radical Prostatectomysupporting
confidence: 57%
See 3 more Smart Citations